Sentiment analysis of public opinion on public housing savings policy (Tapera) on social media “X” - Karina Khansa Thufailah; Biyan Mahesa Albianazwa; Deliana Maulida Ahsanti (Department of Government Science, 2024)
This study aims to analyze public sentiment towards the People's Housing Savings (TAPERA) policy on social media platform X (formerly Twitter). Responses to the Tapera policy can reflect the level of public trust in the government and the agency that manages Tapera. Sentiment analysis can provide an overview of this trust. This study uses a quantitative method with sentiment analysis techniques to measure public reactions based on comments on platform X. Data were collected from several comments related to the TAPERA policy and analyzed using the confusion matrix validation technique to ensure the accuracy of the results. The results showed that more than 90% of public sentiment towards the TAPERA policy was negative. This negative sentiment was mostly triggered by public concerns about salary cuts that were considered burdensome and low trust in the government's ability to manage the funds in a transparent and accountable manner. These findings emphasize the importance of transparency, effective communication, and public participation in the formulation of public policy. These findings are expected to provide insight for stakeholders in formulating policies that are more responsive to the needs and aspirations of the community.